Design Selenium test framework from scratch : architect level - Shetty, Rahul (Packt Publishing, 2018)
"Are you struggling with understanding the Test Automation Frameworks and clearing Top Companies Interviews? Do you have just basic knowledge of Selenium and have a plan to enhance your skills at Architect level? If yes then you are at right place. One Single Course to Master Test Automation Framework with all Latest Technologies available in the globe! This Scratch level program trains you on every aspect of the framework with the practical project, on course completion you will be mastered in Designing Framework and can implement successfully it in your work place."--Resource description page